Complete encapsulation of zeolite supported Co based core with silicalite-1 shell to achieve high gasoline selectivity in Fischer-Tropsch synthesis. (1st March 2018) - Javed, Mudassar; Cheng, Shilin; Zhang, Guihua; Dai, Peiyao; Cao, Yingnan; Lu, Chengxue; Yang, Ruiqin; Xing, Chuang; Shan, Shengdao
Graphical abstract: Highlights: Silicalite-1 based microcapsule catalyst is prepared with hydrothermal synthesis. Silicalite-1 shell is 15 nm thick and it has microporous structure. Prepared catalyst exhibited high gasoline and low CH4 and CO2 selectivity in FTS. Hydrophobic silicalite-1 shell contributes in lowering CO2 and increasing olefins. High gasoline selectivity is attributed to silicalite-1 pore structure. Abstract: Zeolite-based capsule catalysts have exhibited significant results in terms of catalytic activity and product selectivity in Fisher-Tropsch synthesis. Herein, we synthesized a ZSM-5 supported Co based microcapsule catalyst encapsulated by microporous silicalite-1 shell via hydrothermal synthesis process. Synthesized microcapsule catalyst has a uniform microporous structure with an additional stay zone for both reactants as well as product inside its channels and showed significantly high CO conversion rate (68.9%) and gasoline range hydrocarbon selectivity (74.7%) with a low CO2 and CH4 selectivity (2.8% and 8.7%, respectively). This microcapsule catalyst may consider to be used on commercial scale because of its facile preparation method and promising performance.